Analysis of problem-solving ability: Pólya's strategy and positive attitude - Wenny Fitria; Rudi Susilana; Nanang Priatna (Inovasi Kurikulum)
Problem-solving is essential for individuals to face various challenges in the 21st century. Therefore, problem-solving has become a primary goal in mathematics curricula worldwide. However, despite its importance, problem-solving remains one of the most challenging aspects to grasp in mathematics education. Several studies have shown that appropriate strategies and a positive attitude toward problem-solving can help improve students' problem-solving abilities. In this study, the author will examine the implementation of Pólya's mathematical problem-solving strategy. Additionally, the study will explore students' attitudes toward problem-solving and how these attitudes influence their performance. Finally, the research will assess the combined impact of Pólya's strategy and students' attitudes on their problem-solving abilities. This study employs a qualitative approach using content analysis methods. The results show that the top ten students from one of the best schools in Siak Regency still struggle to solve simple problems. This failure is attributed to inappropriate strategies and a lack of a positive attitude toward problem-solving. The study concludes that mastering problem-solving strategies and fostering a positive attitude are crucial for students to become effective problem solvers.